Mobile-Based Garbage Bank Empowerment Education in Jambi City - Erris Erris; Supriatna Supriatna; Sondang Sondang; VA Irmayanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the perceptions, participation, knowledge of housewives in managing the Garbage Bank and provide education on empowering mobile-based Garbage Banks to sort organic and inorganic waste where the management of the Garbage Bank emphasizes. The research method by collecting perceptual data is carried out before being given education to housewives preparing instruments in the form of observations, checklists, interviews and documentation before collecting data conducting discussions and common perceptions about the content of the instrument then expected to have mobile-based application outcomes and making bank empowerment educational materials Garbage that is entered into the google form, the technique of spreading it empowers the Head of the Neighborhood Association, Head of the Garbage Bank, Young Women with the results of the answers of Housewives and Young Women on the Google form, data analysis is carried out. This research is a quantitative study with the Dependent T Test and Paired-Samples T-Test with a 95% confidence level, alpha = 0.05. If the calculated value is less than 0. The statistical test results obtained a value of 0.000, so it can be concluded that there is a significant difference between perception, participation and knowledge before and after mobile-based education on empowering housewives,The statistical test results obtained a value of 0.049, so it can be concluded that there is a significant difference between good knowledge and poor educationin community empowerment through the management of a Waste Bank by means of 3R (reduce, reuse, recycle).As for the conclusions of the study, there are differences in perception, participation, differences in knowledge of housewives before and after education on empowering mobile-based Garbage Banks in Jambi City, the influence of knowledge of housewives on education on empowering Garbage Banks with the use of mobile-based applications in Jambi City.